A new interdisciplinary perspective in the design of early evaluation and intervention programs for children with visual impairment - Mercuriali, Elena; Ceccato, Chiara; Incagli, Francesca; Berto, Giulia; Suppiej, Agnese; Reffo, Maria Eleonora (Frontiers in Pediatrics, 2025)
Vision plays a crucial role in children's early development. Many studies have demonstrated that disturbance of vision affects a child's developmental trajectory, especially if it occurs early in life. The current report introduces an innovative perspective concerning the evaluation of infants and toddlers with visual impairment within a family-centred, interdisciplinary framework. It emphasizes that a collaborative, multi-professional framework is crucial for understanding and addressing the complex needs of children with visual impairment and their families, particularly during the critical early stages of life. The article presents a six-week evaluation program for children with visual impairment, aged 0–24 months, which has been implemented over the past fifteen years at the Robert Hollman Foundation, Italy. This program integrates professionals from various fields, including paediatric ophthalmology, neurology, psychotherapy, and rehabilitation therapy, to comprehensively assess the child's visual and developmental functioning. Central to this approach is the active involvement of caregivers, who are informed, engaged and empowered in relation to their child's needs. The report argues that an interdisciplinary and family-centred evaluation framework is essential for providing tailored support and facilitating effective early intervention, ultimately improving care outcomes for children with visual impairment.